2018
DOI: 10.3389/fpsyt.2018.00105
|View full text |Cite
|
Sign up to set email alerts
|

Language Patterns Discriminate Mild Depression From Normal Sadness and Euthymic State

Abstract: ObjectivesDeviations from typical word use have been previously reported in clinical depression, but language patterns of mild depression (MD), as distinct from normal sadness (NS) and euthymic state, are unknown. In this study, we aimed to apply the linguistic approach as an additional diagnostic key for understanding clinical variability along the continuum of affective states.MethodsWe studied 402 written reports from 124 Russian-speaking patients and 77 healthy controls (HC), including 35 cases of NS, usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 57 publications
2
34
1
Order By: Relevance
“…Precisely, the study provides a measure of those elements of communication that may sustain depressed patients to overcome the difficulties in accessing their inner world and emotions and in regulating their relational distance in interaction with the therapist (Valdés, 2014;Valdés and Krause, 2015). These represent typical aspects of the functioning profile of depressed patients that derive from the first cognitive-affective representations and impact on the development and maintenance of the TA (Levy and Wasserman, 2009;Balsters et al, 2012;Smirnova et al, 2018). We believe, therefore, that these results, on the one hand, may consolidate knowledge on verbal dynamics and, on the other hand, may reveal aspects unexplored in the Italian context on vocal and interruption modes that, together with the former, may guide interventions with this kind of patients to increase the therapeutic effectiveness and lay the foundations for change.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Precisely, the study provides a measure of those elements of communication that may sustain depressed patients to overcome the difficulties in accessing their inner world and emotions and in regulating their relational distance in interaction with the therapist (Valdés, 2014;Valdés and Krause, 2015). These represent typical aspects of the functioning profile of depressed patients that derive from the first cognitive-affective representations and impact on the development and maintenance of the TA (Levy and Wasserman, 2009;Balsters et al, 2012;Smirnova et al, 2018). We believe, therefore, that these results, on the one hand, may consolidate knowledge on verbal dynamics and, on the other hand, may reveal aspects unexplored in the Italian context on vocal and interruption modes that, together with the former, may guide interventions with this kind of patients to increase the therapeutic effectiveness and lay the foundations for change.…”
Section: Discussionmentioning
confidence: 99%
“…Patients, therefore, live the therapeutic relationship and the alliance construction by manifesting different experiential and behavioral modalities through verbal and non-verbal communication (Tomicic et al, 2009;Valdés and Krause, 2015), as an expression of their psychological processes and symptoms (Valdés, 2014;Elvevåg et al, 2016). Depressed patients, in particular, show difficulties in developing and maintaining the TA because of the specific verbal and non-verbal correlates that define their communicative behaviors (Balsters et al, 2012;Smirnova et al, 2018). According to the psychodynamic approach, these behaviors reflect the broad range of depressed patients' defensive, adaptation, and cognition styles deriving from the early cognitive-affective representations where anger and aggression are predominant (Levy and Wasserman, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Taking into account the belief that the way we think is reflected in our language, it is interesting to analyse how people with depression speak, especially when considering aspects other than semantic information. Linguistic structure of patients' verbalizations occurred to be a good diagnostic marker of mild depression (Bernard et al 2016;Rude et al 2004;Smirnova et al 2019) distinguishing it from normal sadness and euthymic state (Smirnova et al 2018), a predictor of future depressive symptoms (Zimmerman et al 2017) and a predictor of suicide (Stirman and Pennebaker 2001). One of the most important psychological theories about language use is the Linguistic Category Model (LCM) introduced by Fiedler (1988, 1991).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…We therefore include these two feature sets in our analyses. Previous studies have shown that people with depression tend to use more personal pronouns [28,47] and past tense verbs [40] in their writing. While De Choudhury et al [13] included the frequencies of pronouns as a feature, differences in other part of speech constructs were not analyzed.…”
Section: Featuresmentioning
confidence: 99%
“…Zimmermann et al [47] showed that the relative frequency of first-person singular pronouns spoken in clinical interviews predicts the severity of future depressive symptoms. Smirnova et al [40] found that Russian speakers with depression used more personal and indefinite pronouns and continuous and past-tense verbs. Van Der Zanden et al [44] showed that "discrepancy words" (e.g: 'would', 'should', 'conflict', 'wish', and 'hope') used by depressed individuals predict treatment outcome and adherence.…”
Section: Related Work In Psychiatry and Psychologymentioning
confidence: 99%